(untitled) (Research, Society and Development, 2021)
This paper aims to reflect on contributions of the Environmental Rationality to Professional Education. It attempts to contribute to teacher education in Professional Education institutions, particularly the Federal Institutes of Education, Science and Technology. The research is theoretical, with a hermeneutical approach, and interpretative and comprehensive potential. The basic elements of analysis are the following: Historical contexts of Professional Education; Epistemological assumptions about the genesis of the Federal Institutes; Organization of the Federal Institute of Rio Grande do Sul. The following ontological principles of Environmental Education have emerged from the analysis: Belonging to the field of knowledge; Pedagogical otherness; Comprehensive circles; Environmental care. The results have evidenced that the Environmental Rationality is in the genesis of the epistemological conception of the Federal Institutes, and that teacher education may potentialize Environmental Education in the institution. It has also been concluded that one of the main alternatives to Environmental Rationality in Professional Education is specific teacher education for Professional Education, i.e. contextualized according to its specificities.